The relationship of capital structure and firms performance: evidence from Malaysian Companies Listed / Fitriani Jasdar - Jasdar, Fitriani (2016)
This study aimed to investigate the relationship of capital structure and firm performance of the Malaysian Companies listed on Main Board Bursa Malaysia during the period from 2009 up until 2014. This study applied on 60 Malaysian companies listed on Bursa Malaysia comprises six sectors which are construction, industrial product, consumer product, property, plant and trading service. This study used panel data approach. This study used Return on Asset (ROA) as proxies for performance, whereas used Long Term Debt to Total Capital ratio, Total Debt to Total Capital ratio and Total Debt to Total Asset as proxies for capital structure. The findings revealed there is positive and negative relationship between the proxies. The results shows different sectors have different relationship between capital structure and firm performance.